Efektivitas Aromaterapi Geranium terhadap Penurunan Nyeri dan Percepatan Penyembuhan Luka Perineum pada Ibu Nifas - Ratih Kumala Dewi; Evita Aurilia Nardina (Politeknik Negeri Jember, 2025)
Perineal pain and lacerations are common postpartum conditions that can disrupt maternal comfort, mobility, and the healing process. Aromatherapy has gained attention as a safe non-pharmacological option to support postpartum recovery. This study examined the effectiveness of geranium aromatherapy in reducing perineal pain and enhancing wound healing among postpartum mothers. A quasi-experimental pretest–posttest design with a control group was used. Forty postpartum mothers with first- or second-degree perineal tears were selected through purposive sampling and allocated to intervention or control groups. Pain intensity was measured using the Visual Analog Scale (VAS), and wound healing was assessed through a structured observation checklist. Statistical analyses included paired t-test, independent t-test, and chi-square test. The intervention group showed a significant reduction in pain scores (p < 0.001) and a higher wound healing rate than the control group (90% vs 50%, p = 0.007). Geranium aromatherapy effectively decreased perineal pain and promoted faster healing, supporting its integration into holistic postpartum care. Keywords: geranium aromatherapy, perineal pain, wound healing, postpartum.